COMMON: uma ferramenta para composição semiautomática de modelos de processos de negócio - Saraiva, Maurício de Oliveira (Universidade do Vale do Rio dos Sinos, 2016)
The evolution of technology has allowed an increasingly better support to the discipline of business process management (BPM). The automation of practices from modeling tools, allows building models to support organizations in the design and management of its processes. In BPM, the transformation and continuous improvement of methods are fundamental to the management of the organization and models of business processes should follow this evolution. To perform the merge of these models, by the transformation of one or more processes, or by merging of organizations, software analysts use the techniques available in the literature. However, frequently they are considered imprecise, by not ensuring the correct integration of models. Consequently, merging business processes models becomes a difficult, error prone task, since existing techniques create composite models difficult to understand based on graphs and generic notation that does not match to the industrial reality. Therefore, this study proposes a merging technique of business process models that combines in a single source, some of the most used techniques available in the literature, and supports merging of models directed to a notation widely known and used by organizations. Furthermore, it also proposes the implementation of a tool, based on this technique, which was created to define the similarity and support the integration of models in a semi-automatic way. Lastly, experimental studies were performed with analysts who solved six scenarios of merging models, both manually and with the help of this tool. The result showed that the proposed technique, in fact, improves the accuracy and reduces composition effort, providing cost savings and increased productivity.
Keywords: Gerenciamento de processos de negócio; Modelos de processos de negócio; Composição de modelos de processos de negócio; BPMN; Business process management; Business process models; Merging business process models; ACCNPQ::Ciências Exatas e da Terra::Ciência da Computação